Evaluation of cardiac functions in juvenile systemic lupus erythematosus with two-dimensional speckle tracking echocardiography. Issue 8 (August 2016) - Dedeoglu, Reyhan; Şahin, Sezgin; Koka, Aida; Öztunç, Funda; Adroviç, Amra; Barut, Kenan; Cengiz, Dicle; Kasapçopur, Özgür
Abstract The aim of this study was to investigate subclinical systolic and diastolic dysfunction in juvenile-onset systemic lupus erythematosus (j-SLE) patients with speckle tracking echocardiography (STE) and the effects of disease activity on left ventricular (LV) regional functions. Thirty-five patients with j-SLE and 30 healthy children (control group) were evaluated between January and August 2015. STE was performed on all patients and controls. Medical records, including diagnosis criteria, age at diagnosis, and duration of disease, were evaluated. SLE disease activity was assessed using the SLE Disease Activity Index (SLEDAI). j-SLE patients had lower ejection fraction than did control subjects but still within normal range. LV end-diastolic and end-systolic dimensions were significantly larger in j-SLE patients (32.43 ± 3.2 vs 28.3 ± 3.1 and 21.1 ± 1.9 vs 18.9.0 ± 2.2, respectively;p = 0.001). There was a significant reduction in longitudinal strain of LV segments in the j-SLE patients compared with controls. J-SLE patients were further divided into subgroups. Group 1 comprised patients having SLEDAI scores >8 at the onset of disease but who improved with therapy during follow-up. Group 2 included j-SLE patients with SLEDAI scores >8 at diagnosis and persistently >4 at the end of follow-up. In the LV mid-inferior and mid-inferolateral segments, STE strain measurements of group 2 were significantly lower than those of group 1 (15.9 ± 6.4 vs 20.0 ± 4.4, 17.9 ± 7.2 vs 23.2 ± 3.8;p = 0.075, p = 0.055, respectively). Simple and non-invasive STE would be helpful in predicting cardiovascular prognosis with new therapeutic medications/interventions or in objectively comparing the effects of immunosuppressive drugs in comparison with preceding STE evaluation.